Bentuk-Bentuk Pelaksanaan Bimbingan Karier Dalam Meningkatkan Prestasi Kerja Karyawan di Pusat Penelitian Kelapa Sawit (PPKS) Medan: Forms of Implementing Career Guidance in Improving Employee Performance at the Medan Oil Palm Research Center (PPKS). - Ahad Syabrianto (Sociocouns: Journal of Islamic Guidance and Counseling, 2023)
This study aims to find out how the forms of implementation of career guidance are carried out by the Palm Oil Research Center (PPKS) to improve employee performance, then find out how career guidance methods are used and to find out how employees respond to the implementation of career guidance. This type of research is a field research (field research) using a qualitative approach. The data collection techniques in this study, namely by using observation, interviews and documentation. The number of informants in this study were three, namely the Head of the HR Subdivision and the Secretariat and the HR Subdivision Staff. The results showed that the form of career guidance carried out at the Palm Oil Research Center (PPKS) used three forms, namely: 1) information career guidance, 2) placement career guidance, 3) orientation career guidance. For the career guidance method used to improve the work performance of the coaching several methods are used, namely: 1) the ABK method (Workload Analysis)), 2) the senior and junior system method, 3) the acceleration method. Then the implementation of career guidance at the Palm Oil Research Center (PPKS), has been effective in its implementation, many employees have benefited from the career guidance, but there is still a need for improvement in its implementation because there are still some employees who have not benefited from the career guidance.